2‐Methoxyestradiol confers neuroprotection and inhibits a maladaptive HIF‐1α response after traumatic brain injury in mice. (2nd April 2014) - Schaible, Eva‐Verena; Windschügl, Julia; Bobkiewicz, Wiesia; Kaburov, Yordan; Dangel, Larissa; Krämer, Tobias; Huang, Changsheng; Sebastiani, Anne; Luh, Clara; Werner, Christian; Engelhard, Kristin; Thal, Serge C.; et al.
Abstract HIF‐1α is pivotal for cellular homeostasis in response to cerebral ischemia. Pharmacological inhibition of HIF‐1α may reduce secondary brain damage by targeting post‐translational mechanisms associated with its proteasomal degradation and nuclear translocation. This study examined the neuroprotective effects of 2‐methoxyestradiol (2ME2), the involved HIF‐1α‐dependent response, and alternative splicing in exon 14 of HIF‐1α (HIF‐1α∆Ex14) after traumatic brain injury (TBI) in mice. Intraperitoneal 2ME2 administration 30 min after TBI caused a dose‐dependent reduction in secondary brain damage after 24 h. 2ME2 was physiologically tolerated, showed no effects on immune cell brain migration, and mitigated trauma‐induced brain expression of neuropathologically relevant HIF‐1α target genes encoding for Plasminogen activator inhibitor 1 and tumor necrosis factor alpha. Moreover, TBI‐induced expression of pro‐apoptotic BNIP3 was attenuated by 2ME2 treatment. Alternatively, spliced HIF‐1α∆Ex14 was substantially up‐regulated from 6 to 48 h after TBI. In vitro, nuclear location and gene transcription activity of HIF‐1α∆Ex14 were impaired compared to full‐length HIF‐1α, but no effects on nuclear translocation of the transcriptional complex partner HIF‐1β were observed. This study demonstrates that 2ME2 confers neuroprotection after TBI. While the role of alternatively spliced HIF‐1α∆Ex14 remains elusive, the in vivo data provide evidence that inhibition of a maladaptive HIF‐1α‐dependent response contributes to the neuroprotective effects of 2ME2. <boxed-text content-type="graphic" id="jnc12708-blkfxd-0001" position="anchor" orientation="portrait"> </boxed-text> We examined neuroprotective effects of 2‐methoxyestradiol (2ME2) and the hypoxia‐inducible factor 1‐α (HIF‐1α) response following traumatic brain injury in mice. Early 2ME2 administration reduced the secondary brain damage and neuronal HIF‐1α probably involving ubiquitin proteasome system‐mediated degradation. The up‐regulation of neuropathological HIF‐1α target genes and pro‐apoptotic BNIP3 protein was attenuated. We propose that the inhibition of a maladaptive HIF‐1α response may contribute to 2ME2‐mediated neuroprotection.